Avaliação da participação de canais de cálcio voltagem-dependentes sobre a resposta pruritogênica em camundongos - Maciel, Izaque de Sousa (2014)
We assessed the effects of pharmacological spinal inhibition of voltage-gated calcium channels (VGCC) in mouse pruritus. The epidural administration of P/Q-type MVIIC or PhTx3.3, L-type verapamil, T-type NNC 55-0396 or R-type SNX-482 VGCC blockers failed to alter the scratching behavior caused by the PAR-2 activator trypsin, injected into the mouse nape skin. Otherwise, trypsin-elicited pruritus was markedly reduced by the spinal administration of preferential N-type VGCC inhibitors MVIIA and Phα1β. C. magus-obtained toxin MVIIA displayed significant effects when dosed from 1 to 4 h before trypsin, whereas the effects of P. nigriventer-derived Phα1β remained for up to 12 h. MVIIA or Phα1β also prevented the itching elicited by intradermal (i.d.) injection of SLIGRL-NH2, compound 48/80 or chloroquine, although they did not affect H2O2-induced itching. Furthermore, the co-administration of MVIIA or Phα1β markedly inhibited the pruritus caused by the spinal injection of gastrin-releasing peptide (GRP), but not morphine. Notably, spinal MVIIA or Phα1β greatly prevented chronic pruritus allied to dry skin. However, either toxin failed to alter the edema formation or neutrophil influx caused by trypsin. In addition, epidural MVIIA or Phα1β did not modify the expression of GRP receptor (GRP-R) in the spinal cord, whilst they brought c-Fos activation to control levels. Finally, the in vitro incubation of MVIIA or Phα1β prevented the calcium influx evoked by the synthetic PAR-2 agonist AC264613 in spinal cord synaptosomes. Data brings novel evidence on itching transmission mechanisms, pointing out the therapeutic relevance of N-type VGCC inhibitors to control refractory pruritus.